Bundled indexed crop insurance and technology practices piloted in Bangladesh, India and Sri Lanka - CGIAR Research Program on Water, Land and Ecosystems (2021)
Based on successful piloting of bundled risk solutions in Bangladesh, India and Sri Lanka, new indexed crop insurance and technology practices are being scaled out by governments and insurance companies.